Konsep Pendidikan Karakter Menurut Abdullah Nashih Ulwan - Najwa Mariam Salsabil; Ani Marlia (CV. Doki Course and Training, 2026)
Negative parenting patterns are often associated with increased juvenile delinquency, which if left unchecked can lead them to deviant behavior. This study aims to analyze the influence of fatherlessness on juvenile delinquency in Makassar Class 1 Prison. The study population involved 105 respondents aged 17–22 years. The instruments used were the fatherlessness scale based on the Hawkskin aspect and the juvenile delinquency scale based on the Jensen aspect. The assumption test showed that the data were normally distributed (kurtosis Y = 1.9036; X = 1.2205) and had a linear relationship (linearity deviation = 0.085). Simple regression analysis revealed that fatherlessness significantly influenced juvenile delinquency with a contribution of 33% and a negative direction of influence. This means that the higher the level of fatherlessness, the tendency to engage in delinquency decreases. This finding confirms that the absence of a father figure does not directly increase juvenile delinquency, but is influenced by other, more complex factors.